PERAN SERTA MASYARAKAT DALAM PENGELOLAAN SAMPAH DI DISTRIK MIMIKA BARU KABUPATEN MIMIKA - agus saling; Tiurlina Siregar; Mujiati Mujiati (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2021)
This study aims to analyze and determine the pattern of waste management, to assess the active role and involvement of the community in waste management through the 3R method (reduce, reuse, recycle). The research methodology uses descriptive quantitative and qualitative descriptive analysis methods. Collecting data through observation, questionnaires, and interviews with the sampling technique used is the Stratified Random Sampling method with a sample of 100 respondents. Through the identification carried out, it was found that the community's preference for waste management was included in the good category. Community participation in the current solid waste management system is still low. The role of stakeholders in waste management is still only normative. The potential and constraints of community participation can be developed into a form of household scale management, a form of communal management, and a form of centralized management. Thus, it was found that in order to find a form of waste management in accordance with local conditions, it was necessary to assess community preferences, development potentials and constraints, as well as the economic potential of solid waste, which was integrated with the current form of management.